Geometric analysis of pin fin heat sinks: Effects of ellipticity and perforation for fin on heat transfer - Merdin Danışmaz (Case Studies in Thermal Engineering)
This study explores the effects of fin cross-sectional geometry on the thermal and hydraulic performance of a pin fin heat sink under turbulent flow conditions. The heat sink design features a base plate measuring 100 mm wide, 100 mm long and 3 mm high with 14 fins arranged in a 4-3-4-3 configuration, utilizing air as the working fluid. The investigation employs CFD simulations to analyze variations in heat sink performance due to different fin geometries, including circular and elliptical cross-sections with and without perforations. Results indicate that elliptical fins, particularly those with a radius ratio of 0.50, significantly enhance heat transfer rates, achieving improvements in the HTPF of up to 90 % compared to traditional circular designs. The study highlights a clear correlation between increasing Re and the Nu, demonstrating the effectiveness of elliptical fins in turbulent flow conditions. However, while perforated fins reduce pressure drop, elliptical designs lead to increased pressure drop due to greater surface area and turbulence effects. Temperature distribution analysis reveals that the maximum temperature at the fin tips decreases with higher ellipticity, indicating improved heat transfer efficiency.